Hakikat Ilmu dalam Al-Qur’an: Fondasi Spiritual dan Pedoman Intelektual - Nuhyatul Mursyidah; Syarif Hidayatullah; Arrafi Rivarianto Ramadhan (AL-BAYAN INSTITUTE, 2023)
Knowledge is seen as a distinction that separates humans from other creatures. In the Qur'an, knowledge encompasses various laws and sciences, indicating that understanding the Qur'an requires knowledge. Knowledgeable individuals hold a noble status, as Allah elevates their rank and highlights the importance of knowledge. This research will examine the essence of knowledge in the Qur'an based on several verses, namely QS. Al-Hud (11): 14, QS. Al-Baqarah (2): 145, QS. Al-Baqarah (2): 32, and QS. Al-Qashas (28): 78. The study employs a qualitative approach with a library research method. Islam teaches humanity to continually learn and positions knowledge in a noble place, emphasizing the importance of being grateful for the knowledge bestowed by Allah, while also recognizing its limitations. Humans are reminded not to be arrogant about their knowledge, as there remain many secrets of the universe yet to be uncovered